Effects of humidity on the morphology of microporous membranes - Park, HC; Hong, JM; Ha, SY; Kang, YS; Ahn, KH (KOREAN SOC INDUSTRIAL ENGINEERING CHEMISTRY, 1998)
:The effect of the water vapor absorption into the cast polymer solution before immersing into the water coagulation bath was systematically studied in the preparation of asymmetric membranes by the phase inversion process. It was observed that both the relative humidity (RH) of the contacting air and the contact time had a pronounced effect on the membrane morphology. The pore size in the top skin layer and the skin layer thickness of membranes increased with the increase in the relative humidity of the contacting air as well as the contact time. When a membrane was prepared by coagulating a poly (ether imide)/1-methyl-2-pyrrolidone solution in a water bath, the longer contact time with water vapor resulted in the larger pores in the top skin layer and also the thicker skin layer. But the membrane morphology was slightly affected by the variance in the RH. When poly (vinyl pyrrolidone) was added in the membrane casting solution, both the contact time and RH had significant effects on the membrane morphology. The morphological change was confirmed by measuring the pure water transport characteristics through the membranes.
Keywords: IMMERSION PRECIPITATION; POLYSULFONE